Abu Dhabi International Petroleum Exhibition and Conference 2014
DOI: 10.2118/171799-ms
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Imbibition Mechanism on Flowback Behavior: A Numerical Study

Abstract: Horizontal drilling and multi-stage hydraulic fracturing are among key technologies that enable the oil and gas industry to unlock unconventional resources. Water-based fracturing fluids are commonly used in massive volumes to hydraulically crack shale formations and transport proppant to keep open the newly created fractures. After hydraulic fracturing implemented to stimulate a well, the clean-up process takes place by flowing back the well. Most shale reservoirs tend to trap and retain the fracturing fluid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 4 publications
0
20
0
Order By: Relevance
“…The parameters of complex fracture network formed after multi-stage fracturing along horizontal wells are unknown, so the typical values of other tight reservoirs [31,40] are assigned here as shown in Table 2. Hydraulic fractures are considered to be propped, while reactivated natural fractures with orthogonal distribution are considered to be un-propped [21]. Since the wellbore flow pressure is always higher than the bubble-point pressure during production, the oil-water two-phase flow can be considered in the simulation process.…”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The parameters of complex fracture network formed after multi-stage fracturing along horizontal wells are unknown, so the typical values of other tight reservoirs [31,40] are assigned here as shown in Table 2. Hydraulic fractures are considered to be propped, while reactivated natural fractures with orthogonal distribution are considered to be un-propped [21]. Since the wellbore flow pressure is always higher than the bubble-point pressure during production, the oil-water two-phase flow can be considered in the simulation process.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Similarly, experimental data showed that the water imbibition capacity of tight shale was very low, even for hydrophilic rock samples [20]. Furthermore, it was difficult to explain the reason for low water recovery efficiency when the spontaneous capillary forces were absent in oil-wet tight rocks [21,22] or the wells were immediately cleaned up without shut-in. By analyzing the pressure transient data, natural fractures that re-opened during fracturing were apparently closed in subsequent production processes [23].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, improvements in hydrocarbon permeability have been observed in field operations after performing well shut-ins (Bertoncello et al, 2014). Furthermore, several studies have shown that well shut-ins after the hydraulic stimulation can dissipate the water into deeper regions of the formation rock (Almulhim et al, 2014;Bertoncello et al, 2014;Cheng, 2012;Dutta et al, 2014;Mahadevan and Sharma, 2005;Longoria et al, 2015). However, the efficacy of a well shut-in depends on the petrophysical properties of the reservoir and a recent laboratory study showed that some reservoir samples regain permeability to the hydrocarbon after a shut-in while others do not (Bostrom et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Li et al (2013) carried out simulation studies by varying several fracture parameters to develop a correlation between early gas production and the key fracture parameters in a shale reservoir. Similarly Almulhim et al (2014) carried out numerical studies on the impact of water imbibition on flowback behavior. Cheng (2012) found correlations between shut-in time and water production rate, gas production rate and water load recovery.…”
Section: Introductionmentioning
confidence: 99%
“…As such, the same average values (e.g. of compressibility) are conventionally assigned for all the porous media in the stimulated reservoir volume (Cheng, 2012;Li et al 2013;Almulhim et al, 2014). This can lead to misleading history-match and erroneous forecast when applied to field data.…”
Section: Introductionmentioning
confidence: 99%